User Experience Analysis on Mobile-Based MOBA Games Using UX Curve Method: Case Study: Mobile Legends - Arianto, Fariz; Az-Zahra, Hanifah Muslimah; Prakoso, Bondan Sapta (Journal of Games, Game Art, and Gamification, 2024)
Nowadays, one of the most commonly used form of entertainment is games. For this reason, every game developer tries to produce the perfect game by providing exciting gameplay, a friendly interface, and gorgeous graphics. Although many developers fail and end up closing their games, there are also some developers who are successful in doing so. One developer who is successful and very active in updating their game is Moonton, with a game called Mobile Legends: Bang Bang. Related to this, researchers want to analyze what kind of experience that the users feel when playing this game so that many users in Asia, especially in Indonesia, download it. To achieve this goal, it requires the UX Curve method which can be used to evaluate user experience over a period of months without taking a long time. With this study, the researchers hope to find out the user's point of view and identify the reasons in the form of features that are favored by users as a proof of why this game is popular. The results of this research can serve as information for developers to develop similar games. In addition to information for developers, readers can also gain insight into the implementation of the UX Curve method for MOBA games. After the research is concluded, it turns out that updates to the game greatly affect the improvement of the general user experience over time. This is evidenced by the number of curves that increase has a greater number of 9 curves, while the stable and decreasing curves only amount to 3. In addition to the number of curves or quantitative data, user reasons are also taken into account as semi-quantitative data. The highest number of user positive reasons is related to ease of use, which is 51 reasons. The majority of user reasons were related to the functionality of the game such as the ease of using new characters and adapting to the game changes.